The Anatomy of an Algol Procedure - London, Ralph; Wassernan, Anthony (University of Wisconsin-Madison Department of Computer Sciences, 1968)
A specific Algol procedure is analyzed in great detail in order to obtain an analysis of exactly what it does. The strategy of analysis is first explained, and the remainder of the paper consists of the written analysis. The main technique is proof by cases.